PENGARUH BIAYA PROMOSI DAN BIAYA DISTRIBUSI TERHADAP LABA BERSIH PADA PT. UNILEVER INDONESIA Tbk. PERIODE 2006-2013 - Muslim, M Tegar (Jurnal Ilmu Manajemen Retail Universitas Muhammadiyah Sukabumi, 2020)
This research aim to determine the effect of promotion costs and distribution costs to net income at PT. Unilever Indonesia Tbk. registered in Indonesia Stock Exchange. The variables used in this research is the cost of the promotion, distribution costs and net income. The sample used is a quarterly financial report to the PT. Unilever Indonesia Tbk. the period 2006-2013, the number of samples in this research there was 32 samples.This research is a descriptive research in which the data was obtained through an internet site and processed using SPPS version 21. Analysis used is multiple linear regression. Analysis was used to determine significant either partially or simultaneously. Partial test results indicate that the cost of the promotion effect on net income and distribution costs also affect the net income. The test results indicate that the simultaneous promotion costs and distribution costs have a significant effect on net income.